Pathogenetische Aspekte der Sepsis-induzierten Mikrozirkulationsstörung und des septischen Schocks = Pathogenetic aspects of sepsis-induced microcirculatory disorders and septic shock - Philipsenburg, Christoph; Siegler, Benedikt Hermann; Schmidt, Karsten; Hofer, Stefan; Weigand, Markus A.; Uhle, Florian (Anästhesiologie & Intensivmedizin, 2016)
Sepsis is a highly relevant clinical problem, yet its pathophysiology is poorly understood. A microcirculatory disorder due to inflammatory changes of the endothelial cells is crucial for the development of sepsis. This review aims to improve the understanding of sepsis pathophysiology by describing cellular mechanisms that are prone to cause microcirculatory disorder. After a short definition of sepsis and microcirculation, it deals with the inflammatory mechanisms and consequences of endothelial damage with special respect to the role of the glycocalyx and the cytoskeleton in maintaining the endothelial barrier and facilitating intercellular communication. It explains the role of nitric oxide as an important regulator of the vasotonus and the mitochondria) dysfunction as contributor to hypoxia as well as mechanical causes of capillary obstruction. Moreover, the influence of the cholinergic system on inflammatory modulation is elucidated. A fully developed micro circulatory disorder leads to hypoxic organ damage via a redistribution of blood flow, increase in diffusion distance and an intracellular incapacity of using oxygen. The protection or restoration of endothelial cell functions could be the key to a successful therapy of sepsis and should therefore be of high importance in today's sepsis research.
Gesehen am 31.08.2017